Dos subespecies nuevas de Phyllodactylus lanei (Sauria: Geckonidae) - CASTRO FRANCO, RUBÉN (Anales del Instituto de Biología serie Zoología, 2009)
TWO NEW SUBSPECIES OF PHYLLODACTYLUS LANEI (SAURIA: GEKKONIDAE) ARE DESCRIBED AND ILUSTRATED; BOTH SUBSPECIES WERW COLLECTED ON ISLANS; ONE ON ISLAS MARIETAS, JALISCO AND THE OTHER ON ISLA LA PEÑA, NAYARIT; A KEY TO THE FOUR SUBSPECIES OF THE SPECIES IS INCLUDED.